PERSPEKTIF FILSAFAT PENDIDIKAN ISLAM TENTANG ALAM DAN LINGKUNGAN - Muhammad Ihsan (State Institute of Islamic Studies (IAIN) Palu, 2007)
Islam is not a religion for mere ritual activities. It is a total system of life. Therefore, Islam orders all people to maintain the equilibrium of ecology; otherwise, they will risk in exploiting it. Based on this, to avoid people from destroying ecology, they have to be educated. In other words, Islamic education must be implemented based on the actual problems of people, including the ecological problem. It is here that the role of Islamic education in formulating ecology ethics is very significant for all people.Kata Kunci: Filsafat pendidikan Islam, alam, lingkungan